Swear Words Used by Students in Daily Communication - Arvian, Elsan; Hadi, Imron (STIBA IEC JAKARTA, 2024)
This research focuses on 1) the classification of swearing sources used by students of STBA JIA and 2) the classification of the use of swearing proposed by students of STBA JIA. The theory used in this research is Wardhaugh's theory (1986:230); Hughes (1991:208); Rothwell (1973:108); Trudgill (1983) to classify sources and reasons or functions of swearing. This research is qualitative with descriptive methods. The data taken came from questionnaire answers by respondents consisting of 14 male students and 43 female students. This research found that there are 12 sources of swearing used by male respondents and 12 sources of swearing used by female respondents. There are a total of 12 sources of invective, consisting of 7 sources based on experts and 5 new sources. Then, regarding the reasons for using swear words, male respondents stated 16 reasons and female respondents stated 18 reasons. The total number of reasons for using swear words in this study was 24. Furthermore, related to research findings based on the classification of swear words, there is no difference in the classification of sources and the reasons for using swearing words between the reasons for male respondents and the reasons for female respondents